AKTIVASI ZEOLIT ALAM SEBAGAI ADSORBEN PEWARNA ALAMI KULIT BUAH NAGA (PITAYA) - Eka Nurul Hidayah; Munasir Munasir (Komunikasi Fisika Indonesia, 2022)
Natural zeolite is one of the alternative adsorbents with good absorption capabilities, including in absorbing color. The adsorption ability of zeolite can be increased by the activation process because it can increase the Si/Al ratio and pore size. Dragon fruit peel is a natural material that can be used as a natural dye because it contains betacyanin pigments which are equivalent to synthetic dyes. This study aimed to investigate the characteristics of activated green and brown zeolite and their adsorption ability on natural dyes of dragon fruit peel. Zeolite was activated chemically using 3M HCl solution and physically through a heating process of 500°C, then characterized using XRD and FTIR. The zeolite adsorption process was carried out with variations in contact time of 30, 60 and 90 minutes and variations in the mass of the adsorbent 0.1, 0.3 and 0.5 grams. The results of XRD analysis showed that the green and brown zeolite contained mordenite, nepheline and quartz minerals. The highest percentage of color degradation in the adsorption process was in brown zeolite at 27.70% at a contact time of 90 minutes and 88.2% at an adsorbent mass of 0.5 grams. Differences in brown zeolite before and after adsorption can be seen from the shift in the wavelength of each functional group due to the interaction with dragon fruit peel.